Inovasi Layanan Drive Thru “Peminjaman dan Pengembalian Buku” di Balai Layanan Perpustakaan DPAD Daerah Istimewa Yogyakarta - Meyza Indriyani; Labibah Zain (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Purpose Research. This research was conducted to determine the innovation of the drive thru service "book borrowing and returning" at the DPAD DIY Library Service Center in meeting the needs of users. Research method. This type of research uses qualitative methods with a descriptive approach. Data collection techniques use observation, interviews, and literature studies. Analysis data. Data analysis techniques are carried out by data reduction, data presentation, and conclusion/data verification.Results. The results showed that drive thru service innovation based on 5 indicators of innovation criteria, namely: 1) has novelty showing that drive thru service innovation is a new idea, idea, and invention in serving users, 2) effectively shows that drive thru service innovation is very effective in helping and facilitating book borrowing and returning, 3) useful shows that drive thru service innovation is needed to meet user needs,  especially for the agency itself, 4) it can be transferred/replicated showing that drive thru service innovation can be used as an example, reference, and applied to other agencies, 5) sustainability shows that drive thru service innovation is strongly supported to be maintained both from the agency and the user community.